PERSEPSI MASYARAKAT DESA SEDAHAN JAYA TERHADAP KEBERADAAN ORANGUTAN DI ZONA PEMANFAATAN TAMAN NASIONAL GUNUNG PALUNG - soni irawan; Sudirman Muin; Siti Masitoh Kartikawati (JURNAL HUTAN LESTARI, 2023)
Gunung Palung National Park must be maintained as an orangutan conservation area and as a life support system between humans and animals called the use zone. There is a relationship between the community and the existence of the Gunung Palung National Park that cannot be separated which causes the community's perception of the existence of orangutans in the TNGP utilization zone This study aims to examine the perception of Sedahan Jaya's community on the existence of orangutans in the Gunung Palung National Park utilization zone, Analyzing the relationship between land ownership, education level, income and land dependency level with the community's perception of the existence of orangutans in the Gunung Palung National Park utilization zone. This study used a survey method with interviews guided by a questionnaire containing several questions to respondents, and data were collected using purposive sampling. The results of this study indicate that community perceptions tend to be negative (50.58%), area of land ownership is positive (50.59%), low-income level (50.58%), low education level (71.76%) and level of dependency is high (54.35%). The positive and insignificant relationship between the level of the land area is (sig (2- tailet) amount of 0.301, and the correlation coefficient score is 0.113). There is a positive and significant relationship between education level and perception (sig (2-tailed) amount of 0.603, correlation coefficient score is 0.057), there is a negative and significant relationship between income level and perception (sig (2-tailed) amount of 0.040, the correlation coefficient score is -0.223) and there is a negative and significant relationship between the level of dependence and perception (sig (2-tailed) of 0.119, the correlation coefficient score is -0.171.Keywords: Perception, Sedahan Jaya Village, Utilization Zone. AbstrakTaman Nasional Gunung Palung harus dijaga sebagai kawasan konservasi orangutan dan sebagai sistem pendukung kehidupan antara manusia dan hewan yang disebut zona penggunaan. .Adanya hubungan antara masyarakat dengan keberadaan Taman Nasional Gunung Palung yang tidak dapat dipisahkan yang menyebabkan persepsi masyarakat terhadap keberadaan orangutan di zona pemanfaatan TNGP Penelitian ini bertujuan untuk menguji persepsi masyarakat Sedahan Jaya terhadap keberadaan orangutan di zona pemanfaatan Taman Nasional Gunung Palung, Menganalisis hubungan antara kepemilikan lahan, tingkat pendidikan, pendapatan dan tingkat ketergantungan lahan dengan persepsi masyarakat tentang keberadaan orangutan di zona pemanfaatan Taman Nasional Gunung Palung. Penelitian ini menggunakan metode survei dengan wawancara yang dipandu oleh kuesioner yang berisi beberapa pertanyaan kepada responden, dan data dikumpulkan menggunakan purposive sampling. Hasil penelitian ini menunjukkan bahwa persepsi masyarakat cenderung negatif (50,58%), luas kepemilikan tanah positif (50,59%), tingkat pendapatan rendah (50,58%), tingkat pendidikan rendah (71,76%) dan tingkat ketergantungan yang tinggi (54,35%). Hubungan positif dan tidak signifikan antara tingkat luas lahan adalah (sig (2- tailet) jumlah 0,301, skor koefisien korelasi adalah 0,113). Ada hubungan positif dan signifikan antara tingkat pendidikan dan persepsi (sig (2-ekor) jumlah 0,603, skor koefisien korelasi adalah 0,057), ada hubungan negatif dan signifikan antara tingkat pendapatan dan persepsi (sig (2-ekor) jumlah 0,040, skor koefisien korelasi adalah -0,223) dan ada hubungan negatif dan signifikan antara tingkat ketergantungan dan persepsi (sig (2-ekor) dari 0,119, skor koefisien korelasi adalah -0,171.Kata kunci: Persepsi, Desa Sedahan Jaya, Zona Pemanfaatan.